Nurse initiated and managed anti-retroviral treatment: An ethical and legal analysis in South Africa. - Ford, Pelisa (My University, 2014)
This research investigated the ethical and legal issues that impact on the urgent implementation of Nurse Initiated and Managed Anti-Retroviral Treatment (NIMART) in South Africa, which is part of the task-shifting strategy recommended by the World Health Organization (WHO) to deal with the human resource shortage that has negatively impacted access to Anti-Retroviral Treatment (ART) in developing countries (WHO;2006). The objectives were to review and analyse the existing legal framework and provisions for NIMART in South Africa; and to identify ethical issues and implications of NIMART within the current legal framework. It analysed the legal issues that impact on the implementation of NIMART within the public health service in South Africa, as well as the ethical basis and implications of NIMART on the practice of nurses in the scale-up of Anti-Retroviral Treatment in Primary Health Care (PHC). A comparative analysis was done with case studies of task-shifting in other developing countries and evidence-based recommendations for an enabling and long-term sustainable ethico-legal approach to task-shifting were established. The research concluded that despite the existing legal framework for NIMART in South Africa being firmly founded in the Constitution and further enabled by health policy, challenges exist in implementation of certain critical aspects of the enabling legislation relating to nurse training and accreditation required for full authorization to practice NIMART and that these technical challenges if not attended to could threaten the long-term sustainability of NIMART.
Keywords: Antiretroviral Therapy, Highly Active; HIV-1--treatment; Acquired Immunodeficiency Syndrome